IMPLEMENTASI METODE WEB ENGINEERING PADA SISTEM INFORMASI KOPERASI SIMPAN PINJAM MAJU BERSAMA SEJAHTERA BERBASIS WEB - Angga Wiranata (Universitas Ma Chung, 2025)
Cooperatives are one type of business that can maximize information sources to provide information that supports the smooth running of business processes accurately, efficiently, quickly, and productively. Koperasi Simpan Pinjam Maju Bersama Sejahtera, located on Jl. Asahan, Marihat Baris, Kec. Siantar, Simalungun Regency, North Sumatra, which is a cooperative engaged in savings and loans. Koperasi Simpan Pinjam Maju Bersama Sejahtera still uses paper in member registration, deposit management, loans, and cash transactions, which causes a lack of effectiveness, data duplication, and recording errors. This research aims to build a system that is able to facilitate the savings and loan cooperative in managing data related to savings and loans. The system is designed web-based, which is designed with a web engineering development method with a flat interest rate implemented into the system. The results showed that the designed system successfully helped improve efficiency in managing cooperative data, including recording loan transactions, payments, and financial reports. Thus, the implementation of the Web Engineering method has proven effective in systematically structuring the stages of system development so as to produce applications that meet user needs.